Qual economia solidária?: os sentidos da emancipação em um curso de formação - Felipe Marques Carabetti Gontijo (2012)
This work studied a course for Training Trainers in Solidarity Economy, part of a public policy of the federal government focused on the development of Solidarity Economy (SE) in the country. In order to understand the strengths and limitations of this course for the dissemination and/or reflection of this theme, as proposed by the ES social movement, it has been proposed to relate and compare among each other the three spaces/moments considered relevant to this analysis: the "pre-conception", the conception, and the implementation of the course. For the construction of the data this work adopted the epistemological stance of Gonzales-Rey of Qualitative Epistemology. The research was divided into two stages, one documental and another ethnographic, given account of three different areas of the course . For the first two spaces it was used documental research. For the course space itself, both documental and education ethnographic were used. Content analysis were applied to organize the information and build the data. After the analysis it was revealed that, in the specific case of the course, the "entrance" of the ES movement in the government, as it is considered by the SENAES Secretary and solidarity economy theorist Paul Singer, does not distort the movement. There is, among the three moments, a consistent sense of emancipation and about the conceptions of solidarity economy. The differences in emphasis or proposals occur more by different objectives of the communications than necessarily by a clear dispute among different ES projects. However, it must be emphasized that, if on one hand, the adoption of a moderate and more palatable discourse by the SENAES can help expand and open doors for ES in spaces not anti-capitalist in principle, on the other, it can make ES more vulnerable to misrepresentations and to be used in opposed directions to its original goals. Finally, it was evaluated that the course presents limitations especially for its short duration to: discuss large and complex topics and allow greater participation by the learners. The strengths were the consistency between the senses of empowerment and conceptions of ES among the three moments, critical content, varieties of visions and emancipatory practices (participation, selfmanagement of some areas of the course, debates, etc.) stimulated during the course.